Immune Response to an 18-Kilodalton Outer Membrane Antigen Identifies Lipoprotein 20 as a Helicobacter pylori Vaccine Candidate - Keenan, Jacqueline (American Society for Microbiology, 2000)
Experiments were performed using the standardized murine model of Helicobacter pylori infection to determine the immunogenicity of H. pylori outer membrane vesicles in immune protection. These vesicles, which are naturally shed from the surface of the bacterium, induce a protective response when administered intragastrically to mice in the presence of cholera holotoxin, despite the absence of the urease enzyme and associated Hsp54 chaperonin. Immunoblotting identified a specific serum immunoglobulin G (IgG) response to an 18-kDa outer membrane protein in a significant number of immunized animals. This commonly expressed, immunodominant protein was subsequently identified as lipoprotein 20 (Lpp20). Hybridoma backpacks secreting an IgG1 subclass monoclonal antibody to Lpp20 were generated in H. pylori-infected mice and were found to significantly reduce bacterial numbers, providing evidence that this surface-exposed antigen is a true vaccine candidate and not merely an antigenic marker for successful, protective immunization.